Genetic analysis of ear, husk, and tassel traits in tropical maize under diverse environments - Kosgei, Titus; Makumbi, Dan; Mageto, Edna; Kavai, Hilda Musula; Ochieng, George O.; Adhiambo, Carolyne A.; Kasango, Joseph S.; Kamau, Rachael M.; Sserumaga, Julius Pyton (Frontiers Media, 2025)
Grain yield (GY) in maize (Zea mays L.) is influenced by multiple component traits, with ear- and tassel-related traits playing a significant role. Despite their importance, these traits receive less emphasis in tropical maize breeding. This study aimed to: (i) assess the inheritance and heterosis of ear and tassel traits, and (ii) investigate their genetic correlation with GY. Thirty tropical maize inbred lines were used to develop 150 hybrids, which were evaluated under artificial Striga hermonthica infestation, managed drought stress, and rainfed conditions over two years. General (GCA) and specific (SCA) combining ability mean squares were significant (P< 0.05) for most traits, indicating the contribution of both additive and nonadditive gene action. GCA sums of squares predominated over SCA, suggesting that additive gene action controlled the inheritance of ear, husk, and tassel traits. Broad-sense heritability was high for husk (H-2 = 0.59-0.89), ear (H-2 = 0.71-0.93), and tassel (H-2 = 0.78-0.95) traits. Fifteen inbred lines exhibited significant positive GCA effects for ear traits, suggesting the presence of favorable alleles associated with increased ear length (ERL) and circumference (ERC). Additionally, 23 inbred lines exhibited favorable GCA effects for reduced tassel size. Mid-parent heterosis for ERL (41%) and ERC (22%) was greater under managed drought stress. Both ERL and ERC were strongly correlated with GY (r(g) = 0.58-0.96), suggesting their suitability for inclusion in a selection index. Path analysis identified ERL and ERC as having significant positive direct effects on GY, while ear aspect had a negative direct effect on GY across all conditions. Selection for ear and tassel traits in tropical maize is recommended to develop more efficient inbred lines for higher grain yield.